PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA METODE GENIUS LEARNING DENGAN PENDEKATAN OPEN ENDED POKOK BAHASAN SISTEM PERSAMAAN LINIER DUA VARIABEL DI SEKOLAH MENENGAH PERTAMA (SMP) KELAS VIII SEMESTER GASAL - Noviliya, Ira Noviliya; Setiawan, Toto Bara; Setiawani, Susi (KadikmA, 2013)
Abstract.Genius Learning method of Open Ended approach is a learning that creates a positive and conducive in learning process. So, the student can improve their logical thinking and creative thinking.The research aims to know the process and resultof Development ofMathematics Learning MaterialsBased on Genius Learning Method with Open Ended Approach for Linier Equation System in Two Variable of Junior High School at Eight Grade of Odd Semester.The development of learning materials refers toThiagarajan, Semmel and Semmel Model ( 4-D Model). The product of the research are lesson plan, student book, worksheet, and evaluation test. This product has been implemented in learning of Genius Learning Method with Open Ended in all of learning sets. Based on validation process and tryout the learning sets can be concluded that the learning sets had been appropriate with validate, practice, and effective criteria. Key Words: Genius Learning Method, Open Ended Approach,Linier Equation System in Two Variable, 4-D Model.